OUTCOME AND TRANSFORMATION OF FEBRILE SEIZURES IN CHILDREN (DATA OF SVT. LUKA'S INSTITUTE OF CHILD NEUROLOGY & EPILEPSY) - M. B. Mironov; K. Yu. Mukhin (Русский журнал детской неврологии)
According to definition, febrile seizures — benign, age-dependent, genetically predisposed condition in which the brain is susceptible to epileptic seizures, occurring in response to the fever. The article presents the outcome and transformation of febrile seizures in children by data of Svt. Luka's Institute of child neurology & epilepsy. The authors found, thatfebrile seizures can occur at onset of 21 epileptic syndromes with different etiologic factors and outcome. The clinical characteristics, EEG and neuroimaging data, as well as the effectiveness of antiepileptic drugs and prognosis of differentforms of epilepsy with febrile seizures in history are described in detail.